Changing the Emergency Department's Practice of Rapid Sequence Intubation to Reduce the Incidence of Hypoxia. (October 2017) - Gooch, Michael D.; Roberts, Eric
Abstract : Rapid sequence intubation (RSI) is an advanced procedure performed by nurse practitioners in the emergency department (ED). Hypoxia is one of the most common complications associated with RSI, which may lead to serious sequela, including death. Hypoxia may result from medications that are given to facilitate the procedure or the underlying disease process. Without preventive measures, oxygen levels may fall rapidly when patients are no longer actively breathing. The incidence of RSI-induced hypoxia may be mitigated with proper education, preoxygenation, positioning, and the utilization of passive (apneic) oxygenation. The purpose of this project was to determine whether RSI practice could be changed through education and implementation of an evidence-based protocol in the ED of a hospital in south central United States. Baseline practice was determined by chart audits and compared with practice after educational sessions and protocol implementation. Change occurred as evidenced by an increase in the utilization of all 3 hypoxia prevention interventions included in the protocol. Staff education and utilization of a protocol changed the care provided, which can influence patient outcomes and decrease the incidence of RSI-induced hypoxia.